Morphological variation theoretical and empirical perspectives - Schallert, Oliver; Dammel, Antje (John Benjamins Publishing Company, 2019)
Morphological variation is a rather young, yet fascinating topic to study in its own right because it offers challenging evidence both for the autonomy of morphology (morphomic processes) as well as for its tight interconnection with other grammatical domains, notably phonology and syntax. Covering a wide range of phenomena (e.g. negation structures, form function-mismatches in the verbal and nominal domain, loss of morphosyntactic feature values, etc.), the contributions to this volume combine in-depth empirical studies with the explanatory potential of modern theories of grammar as well as approaches for capturing and modelling microtypological diversit
CRIS-Team Scopus Importer:2024-10-21
Keywords: Linguistics; Morphology; Theoretical linguistics; Sociolinguistics and Dialectology; Germanic linguistics; Syntax